2013
DOI: 10.1016/j.parkreldis.2012.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and profile of Restless Legs Syndrome in Parkinson's disease and other neurodegenerative disorders: A case-control study

Abstract: Our study found a higher prevalence of RLS in PD compared to healthy controls or other parkinsonian disorders. Apart from PDSS score, there was no significant difference in the clinical characteristics of PD patients with and without RLS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
60
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 29 publications
6
60
2
5
Order By: Relevance
“…A maioria dos estudos que determinou a prevalência de SPI utilizou os critérios do International RLS Study group para o diagnóstico 3,[12][13][14]16 . Em relação ao desenho do estudo, apenas um estudo era longitudinal 12 e os demais eram transversais 3,4,[13][14][15][16] . Três estudos utilizaram idosos saudáveis como grupo controle e também podem ser classificados como caso-controle 4,15,16 .…”
Section: Resultsunclassified
See 3 more Smart Citations
“…A maioria dos estudos que determinou a prevalência de SPI utilizou os critérios do International RLS Study group para o diagnóstico 3,[12][13][14]16 . Em relação ao desenho do estudo, apenas um estudo era longitudinal 12 e os demais eram transversais 3,4,[13][14][15][16] . Três estudos utilizaram idosos saudáveis como grupo controle e também podem ser classificados como caso-controle 4,15,16 .…”
Section: Resultsunclassified
“…Em relação ao desenho do estudo, apenas um estudo era longitudinal 12 e os demais eram transversais 3,4,[13][14][15][16] . Três estudos utilizaram idosos saudáveis como grupo controle e também podem ser classificados como caso-controle 4,15,16 . A dificuldade dos pacientes em responder às questões elaboradas para identificação da SPI foi investigada por um estudo 13 .…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Previous prevalence studies showed an association of the two conditions with various reported incidence that varied from 0% to 50% often considered as due to ethnic differences [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. However, most of the previous studied didn't exclude secondary RLS [3,[5][6][7][8][9][10][11][12][13][14][16][17][18]. Leg motor restlessness (LMR), which is recently regarded as a kind of "focal akathisia" [19], was described in 2011 as a desire to move the limbs usually associated with paresthesias/dysesthesias but not fulfilling the full RLS criteria [2].…”
Section: Introductionmentioning
confidence: 99%